Literasi Artificial Intelligence dan Tabayyun: Mengatasi Bias Gender dan Kekerasan Berbasis Gender Online - Al Rozi, Isyfi Anny Azmi (Jurnal Komunikasi Islam, 2025)
Artificial Intelligence (AI) and its various products have become an inseparable part of social life, while simultaneously presenting challenges for humans, including issues related to gender bias and online gender-based violence. Using a literature review approach, this study reveals the relevance of the Islamic principle of tabayyun as a form of AI literacy that plays a crucial role in recognizing and addressing gender bias and online gender-based violence in AI-based technologies. In this context, tabayyun fosters analytical, critical, and ethical skills in the process of understanding and disseminating information as part of AI-driven technological practices. Integrating AI literacy, the principles of tabayyun, and digital education offers a solution for creating a more inclusive system, reducing gender bias, and enhancing digital security.